SOCIAL CHANGE IN CHILDREN ISLAMIC EDUCATION AFTER EARTHQUAKE CATASTROPHE PALU CITY - Rustina, Rustina; Suharnis, Suharnis (Hunafa: Jurnal Studia Islamika, 2022)
The purpose of this study was to examine Post-Earthquake Social Changes on Children's Islamic Education in Palu, Petobo Village. Based on the title of this research, the authors reveal the problem, such as How the Forms of Post-Earthquake Social Changes on Children's Education in Petobo Village and Anticipation of what is done in dealing with the Social Changes in Post-Earthquake Children's Education in Petobo Village. This study used quaitative method with a case study approach. The case study in this paper is comunities in Palu which has experience the tsunami and earthquake chatastrhophee. Data was collected through in-depth interview, field observation, and written document. The results of this study show that the form of social change in children's Islamic education after the earthquake is the occurrence of changes in behavior because of physical or natural environmental factors, social environment, economics, infrastructure factors, and factors that decrease children's motivation due to environmental and infrastructure damage. As an implication, it is necessary to develop Islamic education through a humanistic approach because of social change. It must focus on Islamic education, especially in areas affected by earthquakes and liquefaction. The limitation of this research is that it only focuses on social change in the context of education. In the future, there is a need for other research that also examines social change as a whole.